Alguns cálculos de Ends de Grupos - Silva, Mateus Fernando Araújo; Coelho, Francielle Rodrigues de Castro (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2023)
The Theory of Ends of Groups is very relevant in Homological Algebra. In this area, the concept of group ends, algebraically defined by Specker in 1950, is related to the dimension of a quotient space over Z_2.In this work, the main objective is to present concepts and results on ends of a group G, e(G). More specifically, we compute the number of ends of finite groups, infinite cyclic groups, and uncountable groups.